Final answer:
To find the combined function h(x), we need to add the functions f(x) and g(x). Using the given functions, we can substitute these values into the expression for h(x) = f(x) + g(x) and simplify.
Step-by-step explanation:
To find the combined function h(x), we need to add the functions f(x) and g(x). Using the given functions:
f(x) = 4x + 5
g(x) = x² - 10x + 10
We can substitute these values into the expression for h(x) = f(x) + g(x) and simplify:
h(x) = (4x + 5) + (x² - 10x + 10)
h(x) = x² - 6x + 15
Now, we can fill out the table for h(x) by evaluating the function for different values of x:
- x = 0: h(0) = (0²) - 6(0) + 15 = 15
- x = 1: h(1) = (1²) - 6(1) + 15 = 10
- x = 2: h(2) = (2²) - 6(2) + 15 = 7
- x = 3: h(3) = (3²) - 6(3) + 15 = 6
- x = 4: h(4) = (4²) - 6(4) + 15 = 7